The comparison between two age estimation methods based on human teeth - Żądzińska, Elżbieta; Drusini, Andrea G.; Carrara, Nicola (Anthropological Review, 2000)
From among age estimation procedures we chose two for comparison. One of them is the standard method based on root dentin transparency; the other one is based on coronal pulp cavity heigth. The material consisted of X-ray photographs and longitudinally sectioned teeth of 276 individuals (174 males and 102 females) of known age. The comparison shows that the poorly known TCI method is at least as precise as the most widely applied and acknowledged procedure based on longitudinal sections of teeth.